Developing Common Metrics for the Clinical and Translational Science Awards (CTSAs): Lessons Learned. Issue 5 (15th June 2015) - Rubio, Doris M.; Blank, Arthur E.; Dozier, Ann; Hites, Lisle; Gilliam, Victoria A.; Hunt, Joe; Rainwater, Julie; Trochim, William M.
Abstract: The National Institutes of Health (NIH) Roadmap for Medical Research initiative, funded by the NIH Common Fund and offered through the Clinical and Translational Science Award (CTSA) program, developed more than 60 unique models for achieving the NIH goal of accelerating discoveries toward better public health. The variety of these models enabled participating academic centers to experiment with different approaches to fit their research environment. A central challenge related to the diversity of approaches is the ability to determine the success and contribution of each model. This paper describes the effort by the Evaluation Key Function Committee to develop and test a methodology for identifying a set of common metrics to assess the efficiency of clinical research processes and for pilot testing these processes for collecting and analyzing metrics. The project involved more than one‐fourth of all CTSAs and resulted in useful information regarding the challenges in developing common metrics, the complexity and costs of acquiring data for the metrics, and limitations on the utility of the metrics in assessing clinical research performance. The results of this process led to the identification of lessons learned and recommendations for development and use of common metrics to evaluate the CTSA effort.